MYOFIBROBLASTOMA ACCOMPANIED WITH BILATERAL GYNECOMASTIA - Aynur Solak; İlhami Solak; Berhan Genç (European Journal of Breast Health, 2013)

(untitled)
Myofibroblastoma (MFB) of the breast is an uncommon benign tumor. It is more common in men. In this report we present a case of an 65 year old male patient presenting with a firm breast lump diagnosed as myofibroblastoma and confirmed by diffuse positivity of CD34 immunohistochemical stain.Our patient had radical orchiectomy surgery about four years previously and he received estrogen therapy. Therefore, he had bilateral gynecomastia.The breast lump had grown in the previous four years, also. To the best of our knowledge, only one case of myofibroblastoma arising in a context of bilateral gynecomastia has been reported in the literature.